2012
DOI: 10.1002/art.34332
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Genotype, phenotype, and clinical course in five patients with PAPA syndrome (pyogenic sterile arthritis, pyoderma gangrenosum, and acne)

Abstract: Objective To describe the genotypes, phenotypes, immunophenotypes, and treatments of PAPA syndrome (pyogenic sterile arthritis, pyoderma gangrenosum, and acne), a rare autoinflammatory disease, in 5 patients. Methods Clinical information was gathered from medical records and through interviews with 5 patients from 4 kindreds. PSTPIP1 (CD2BP1) exon 10 and exon 11 sequencing was performed in each patient. Neutrophil granule content and cytokine levels were determined in plasma and stimulated peripheral blood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
150
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 17 publications
3
150
0
9
Order By: Relevance
“…The clinical manifestations of this disease are variable, and as observed in our present case, the penetrance of the mutations in the causative gene, PSTPIP1, might be variable in the context of the same family 2,3 .…”
Section: To the Editorsupporting
confidence: 49%
See 1 more Smart Citation
“…The clinical manifestations of this disease are variable, and as observed in our present case, the penetrance of the mutations in the causative gene, PSTPIP1, might be variable in the context of the same family 2,3 .…”
Section: To the Editorsupporting
confidence: 49%
“…In a study, Demidowich, et al reported the occurrence of an osteomyelitis in 1 patient belonging to a small cohort of patients with PAPA. However, a detailed description of radiological and histological findings was not available 3 .…”
Section: To the Editormentioning
confidence: 99%
“…Typically, pyogenic sterile arthritis recurs in childhood and is often triggered by minor trauma. These symptoms tend to improve by adolescence, while the skin manifestations, pyoderma gangrenosum and severe cystic acne exacerbate instead [3,4]. The molecular mechanism by which mutation in the PSTPIP1 causes PAPA syndrome remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Up to this date, three mutations related to this diseased have been identified in the CD2BP1 gene, responsible for synthesizing the CD2BP1 protein. 46 It has been proposed that the mutated protein has a higher binding affinity for the pyrin protein, thus leading to an increased susceptibility to inflammation. Clinical symptoms tend to respond to oral corticosteroids; however, corticosteroid-refractory patients have shown improvement with anti-IL-1 and TNFblockers.…”
Section: Papa Syndromementioning
confidence: 99%
“…Clinical symptoms tend to respond to oral corticosteroids; however, corticosteroid-refractory patients have shown improvement with anti-IL-1 and TNFblockers. 14,46,48 The PAPA syndrome is the most difficult autoinflammatory disease to manage from a clinical standpoint.…”
Section: Papa Syndromementioning
confidence: 99%